PERAN MODUL AJAR TERHADAP MOTIVASI BELAJAR SISWA - Pilenia Pilenia; Olivtia Olivtia; Paulina Paulina (CV. ADIBA AISHA AMIRA, 2025)
This study aims to explore the role of open modules in improving students' learning motivation at SMKS Kristen Palangka Raya. The focus of the study is directed at how teaching modules designed according to students' needs can influence aspects of learning motivation, such as interest, involvement, and perseverance. The teaching modules used are contextual, with content that is relevant to students' daily lives. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with 3 students and 1 teacher, classroom observations during the implementation of the open module, and document analysis in the form of student assignment results. The results of the interviews and observations are explained using thematic analysis techniques. As a complement, an assessment table is prepared to reflect indicators of learning motivation, such as the frequency of student participation in discussions, enthusiasm for completing assignments, and responses to learning challenges. The results of the study show that teaching modules have a positive impact on students' learning motivation. This is indicated by increased active participation of students during learning, increased confidence in answering questions, and enthusiasm for completing the assigned tasks. Teachers expressed that teaching modules helped them create more focused and enjoyable learning. Students also felt that the material in the open module was easier to understand and relevant to their lives. In conclusion, open modules play a significant role in increasing students' learning motivation at SMKS Kristen Palangka Raya. This study recommends the development of more inclusive and creative teaching modules to support various learning styles of students.